The Effect of Project-based Learning on the Improvement of Listening Skills in Junior High School Students - Nifriza, Ifna; Rahmalia, Indah; Reswary, Dahayu Annora (Linguistic, English Education and Art (LEEA) Journal, 2025)
This study aims to determine the effect of Project-Based Learning (PBL) on the improvement of English listening skills in junior high school students. The research method used is a quasi-experimental design with a pretest-posttest control group. The research sample consists of 60 junior high school students divided into two groups: an experimental group that applies PBL and a control group that uses conventional teaching methods. Data were collected through listening tests before and after the treatment. Data analysis using a t-test showed a significant improvement in the listening skills of students taught with PBL compared to the control group. These findings indicate that PBL is effective in enhancing the English listening skills of junior high school students. The implication of this study is the importance of implementing innovative teaching methods such as PBL in English language teaching. Keywords: English, Junior High School Students, Listening Skills, Project-Based Learning